Hérnia hiatal - aspectos clínicos e endoscópicos: análise de 100 casos - OLIVEIRA, Carlos Cunha (2022)
The Hiatal Hernias are pathologic entities anatomicaly defined, but still with uncertain genesis and nonspecific clinical profile. Although a few instances are congenital, esophageal hiatal hernias usually appear later in life and are considered to be acquired. In order to investigate the hiatal hernias genesis, and so characterize the symptomatology, it had been studied the medical profiles of 100 patients, 72 male and 28 female, ages between 15 to 74 years old, attended on Dr Tude Menezes Gastroenterology and Endoscope Clinic, located at Belém, Pará, on period from January 2004 to June 2005. It had been studied the patients most frequent symptoms, hiatal hernia kinds diagnosed by high digestive endoscopy and associated endoscopic pathologies, and so Helicobacter pylori research. The most frequent symptoms were pyrosis and postprandial sensation. All cases were sliding hernias and the most frequent associated pathology was gastritis. Helicobacter pylori research was positive in 46% cases. Establish a trustworthy clinical profile requires more studies, for a better definition and, then make easy the early and efficient diagnosis of hiatal hernias and so the right therapy can be set up.